2004
DOI: 10.1093/ps/83.1.119
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Retention by Water- and Air-Chilled Chicken Broilers During Processing and Cutup Operations

Abstract: The objective of this study was to evaluate effects of storage and cutting on moisture retention by air- and water-chilled broiler chickens. Sixty-four broilers were slaughtered, chilled by cold air or immersion in water, stored over night, cut into fore- and hindquarters, and then stored an additional 24 h. Air chilling conditions were 4 degrees C with air velocity of 2.2 m3/min. Water chilling conditions were 1 degree C with mechanical agitation. Moisture absorption and retention were observed as weight chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 13 publications
2
14
0
Order By: Relevance
“…NPLS marination promoted higher carcass marinade uptake compared with water marination (p<0.05), indicating that the additive included in the marinade solution increased carcass water absorption. These results are in agreement with previous studies, which reported about 4 to 8% water absorption in poultry carcasses immersed in marinades (Veerkamp, 1990;Young &Smith 2004;Huezo et al, 2007Jeong et al, 2011Demirok et al, 2013). The increase in carcass weight of both marinated treatments was probably due to water absorption during marination.…”
Section: Carcass Marinade Uptake and Parts Yieldsupporting
confidence: 92%
“…NPLS marination promoted higher carcass marinade uptake compared with water marination (p<0.05), indicating that the additive included in the marinade solution increased carcass water absorption. These results are in agreement with previous studies, which reported about 4 to 8% water absorption in poultry carcasses immersed in marinades (Veerkamp, 1990;Young &Smith 2004;Huezo et al, 2007Jeong et al, 2011Demirok et al, 2013). The increase in carcass weight of both marinated treatments was probably due to water absorption during marination.…”
Section: Carcass Marinade Uptake and Parts Yieldsupporting
confidence: 92%
“…The microbial quality of the air-chilled product is better than that of a water-chilled product (Barbut, 2002;Sanchez et al, 2002). Young and Smith (2004) reported that air-chilled carcasses lost 0.68% of their postslaughter weight in storage prior to cutting but lost no more during cutting or postcutting storage. On other hand water chilled carcasses absorbed 11.7% moisture in the chillers, of which 4.72% was lost within 24 h of intact carcass storage, 0.98% was lost during cutting and 2.10% was lost during storage resulting in 3.9% net water retention.…”
Section: Chillingmentioning
confidence: 99%
“…In these tanks, the carcasses are displaced by means of an endless screw in counter-current with the cooling water flow (JAMES et al, 2006;CARCIOFI;LAURINDO, 2007). In European countries, the air cooling of poultry carcasses is more common because of the policies that restrict the usage of immersion chilling (YOUNG;SMITH, 2004;JAMES et al, 2006).…”
Section: Introductionmentioning
confidence: 99%